RELATIONSHIP BETWEEN IMPLIED PRODUCTIVITY OF RETENTION AND THE STOCK PRICE IN THE INDONESIA STOCK EXCHANGE - Kuntara, Antonius Diksa (Jurnal Fakultas Ekonomi, 2012)
The study is investigating the effect of the announcement of dividend policy to companys share price in a capital market in Indonesia. Specifically, the study is examining the implied productivity of retention and the share price around the announcement of companys dividend policy. Through the research question "Are the implied productivity of retention and stock price related?" the study is analyzing the correlation between the implied productivity of retention and companys share price. The study is also investigating the correkation between the implied productivity of retention with the moving price, which is the price before the announcement and after the announcement of divedend policy. The data used is gathered from all companies paying cash dividend from 2000-2008. After selecting all criteria, there are 210 companies with 635 company-days of announcement to analyze. As the research is quantitative correlation study, the data is analyzed using a statistical tool, the Pearson-bivariate correlation analysis using SPSS series 12.0. The study resulted that there is a negative but not significant correlation.